Current advancement of flexible dye sensitized solar cell: A review - Noorasid N.S.; Arith F.; Mustafa A.N.; Azam M.A.; Mahalingam S.; Chelvanathan P.; Amin N. (Elsevier GmbH, 2023)
Deposition; Dye-sensitized solar cells; Electrophoresis; II-VI semiconductors; Solar power generation; Substrates; Titanium dioxide; Zinc oxide; 'current; Dye- sensitized solar cells; Flexible; Flexible dye sensitized solar cell; High flexibility; Lows-temperatures; Photovoltaics; Silicon-based; Titania isopropoxide(IV); Titanium Isopropoxide; Temperature